Extraoral Retrograde Root Canal Filling of an Orthodontic Induced External Root Resorption Using CEM Cement - Kheirieh, Sanam; Fazlyab, Mahta; Torabzadeh, Hassan; Eghbal, Mohamad Jafar (Iranian Endodontic Journal, 2014)
Inflammatory external root resorption (IERR) after orthodontic treatments is an unusual complication. This case report describes a non-vital maxillary premolar with symptomatic extensive IERR (with a crown/root ratio of 1:1) after receiving orthodontic treatment. The first appointment included drainage, chemo-mechanical preparation of the canal and intra-canal medication with calcium hydroxide (CH) along with prescription of analgesic/antibiotic. The subsequent one-week follow-up revealed the persistence of symptoms and formation of a sinus tract. Finally, extraoral endodontic treatment was planned; the tooth was atraumatically extracted and retrograde root canal filling with calcium enriched mixture (CEM) cement was placed followed by tooth replantation. Clinical signs/symptoms subsided during 7 days postoperatively. The sinus tract also resolved after one week. Six-month and one-year follow-ups revealed complete healing and a fully functional asymptomatic tooth. This case study showed favorable outcomes in a refractory periapical lesion associated with orthodontically induced extensive IERR. The chemical as well as biological properties of CEM cement may be a suitable endodontic biomaterial for these cases.